Runoff and Soil Loss under Different Crop Cover in Red Soils of Western Central Tableland Agro-climatic Zone of Orissa - M. M. Mishra,; J. C. Paul,; J. N. Mishra, (Journal of Soil and Water Conservation, 2022)
A field experiment was conducted to study the effect of various remunerative crops, grown in ridge and furrow system, on runoff, soil loss, crop yield and its economics. The experiment was performed on a nearly level land (1.6 per cent slope) with clay loam soil during 2003 and 2004 at village Kadalipali, Puintala block of Bolangir district that fells under in the Western Central Tableland Agro-climatic Zone of Orissa. The different crops grown under ridge and furrow system were cowpea, okra, maize, groundnut and pigeon pea during kharif season. Both the runoff and soil loss were less under cowpea compared to okra, groundnut, maize and pigeon pea. The maximum runoff of 26.55 per cent of rainfall was observed for pigeonpea and minimum of 23.75% for cowpea. The soil loss under cowpea was 21.6, 29.2, 31.8 and 35.3 per cent less as compared to okra, groundnut, maize and pigeonpea respectively. The average net return of cowpea is Rs 21120/ha, followed by okra (Rs. 17580/ha), groundnut (Rs 10422/ha), maize (Rs 5688/ha) and pigeonpea (Rs 31 10/ha). Accordingly, the highest benefit cost ratio was recorded for cowpea (2.76) followed by okra (1.89), groundnut (1.67), maize (1.44) and pigeonpea (1.25). Among the five different crops grown, cowpea was found to be most remunerative crop that was found to reduce runoff and soil loss more effectively.